Opicapone Pharmacokinetics and Effects on Catechol-O-Methyltransferase Activity and Levodopa Pharmacokinetics in Patients With Parkinson Disease Receiving Carbidopa/Levodopa. Issue 2 (21st March 2023) - LeWitt, Peter; Liang, Grace S.; Olanow, C. Warren; Kieburtz, Karl D.; Jimenez, Roland; Olson, Kurt; Klepitskaya, Olga; Loewen, Gordon
Abstract : Objectives: Levodopa (LD) administered with dopa decarboxylase inhibitor is predominantly metabolized in the periphery by catechol- O -methyltransferase (COMT) to 3- O -methyldopa (3-OMD). Catechol- O -methyltransferase inhibition can improve treatment outcomes by decreasing variability in circulating LD concentrations. Opicapone is a once-daily COMT inhibitor approved in the US adjunctive to carbidopa (CD)/LD in patients with Parkinson disease experiencing "OFF" episodes. This study aimed to evaluate the pharmacokinetics and pharmacodynamics of once-daily opicapone 50 mg adjunctive to CD/LD in patients with stable Parkinson disease. Methods: Once-daily opicapone 50 mg was administered the evenings of days 1 to 14. Participants were randomized to receive CD/LD (25/100 mg) every 3 or 4 hours (Q3H or Q4H). Participants received Q3H or Q4H CD/LD on days 1, 2, and 15 and their usual CD/LD regimen on other days. Serial blood samples were collected to determine plasma opicapone, LD, and 3-OMD concentrations and erythrocyte soluble COMT (S-COMT) activity. The effects of opicapone on S-COMT, LD, and 3-OMD were assessed. Mean (SD) values are presented. Results: Sixteen participants were enrolled. At steady-state (day 14), opicapone C max (peak plasma concentration) and AUC0-last (area under the curve-time curve) were 459 ± 252 ng/mL and 2022 ± 783 ng/mL·h, respectively. Maximum COMT inhibition was 83.4 ± 4.9% of baseline on day 14. After opicapone administration, LD total AUC, peak concentration, and trough concentration increased; peak-to-trough fluctuation index decreased. Correspondingly, 3-OMD total AUC, peak concentration, and trough concentration decreased. Conclusions: Adding once-daily opicapone 50 mg to LD resulted in marked and extended COMT inhibition, which increased systemic exposure to LD. These changes translated into higher trough concentrations and decreased peak-to-trough fluctuations for LD.